2007
DOI: 10.1002/humu.20500
|View full text |Cite
|
Sign up to set email alerts
|

Autosomal dominant anhidrotic ectodermal dysplasias at the EDARADD locus

Abstract: Anhidrotic ectodermal dysplasia (EDA) is a disorder of ectodermal differentiation characterized by sparse hair, abnormal or missing teeth, and inability to sweat. X-linked EDA is the most common form, caused by mutations in the EDA gene, which encodes ectodysplasin, a member of the tumor necrosis factor (TNF) family. Autosomal dominant and recessive forms of EDA have been also described and are accounted for by two genes. Mutations in EDAR, encoding a TNF receptor (EDAR) cause both dominant and recessive forms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
67
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(69 citation statements)
references
References 37 publications
1
67
0
1
Order By: Relevance
“…implicated in oncogenesis and several developmental processes associated with HED/EDA (Bal et al, 2007;Headon et al, 2001;Cluzeau et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…implicated in oncogenesis and several developmental processes associated with HED/EDA (Bal et al, 2007;Headon et al, 2001;Cluzeau et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In most cases, HED shows an X-linked recessive inheritance pattern (OMIM 305100) while a minority of HED is inherited as an autosomal-dominant (OMIM 129490) or autosomal-recessive trait (OMIM 224900). It has been shown that X-linked HED is caused by mutations in the EDA gene [1], while autosomal forms of HED are caused by mutations in either the EDAR [2] or the EDARADD [3,4] genes. The EDA gene encodes various isoforms of a type II transmembrane protein through alternative splicing [5,6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Mutations in EDAR (2q11-q13, MIM 604095), which encodes the EDA receptor (EDAR, a TNF receptor) can cause either dominant or recessive forms, and is mutated in approximately 25% of non-EDA-related HED. [6][7][8][9][10][11][12][13][14] Mutations in the EDARADD gene (1q42-q43, MIM 606603), which encodes the EDAR-associated death domain (EDARADD), have been shown to cause either autosomal recessive or dominant HED. However, only two HED families with EDARADD mutations have been reported to date, 13,14 and the incidence of EDARADD mutations in HED remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…The dominant one is thought to act by a dominant negative effect, as it interferes with wild-type EDARADD. 13 We have screened for EDARADD mutations 28 HED patients in whom mutations in both the EDA and EDAR genes were excluded by direct sequencing. 7 We identified only one mutation, a 6-bp homozygous in-frame deletion, demonstrating that EDARADD is rarely implicated in HED patients (one of 136 of the initial cohort, < 1%).…”
Section: Discussionmentioning
confidence: 99%